PENANAMAN NILAI-NILAI KARAKTER SISWA DALAM UPAYA PENCEGAHAN TERJADINYA 3 DOSA BESAR DUNIA PENDIDIKAN - Rafika Nuriafuri; Dini Rakhmawati; Arry Handayani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Particularly in the field of education, character education is still severely inadequate today. The crimes perpetrated by primary school pupils, who are often more impacted by cognitive and contextual factors than their character development, demonstrate the lack of character education. There's a lot of nasty conduct going on these days. It has recently come to light that there are "three major sins" that are causing serious problems for Indonesia's educational system. Bullying, sexual assault, and intolerance are the three main sins. These three items have the potential to hinder the development of a positive learning environment. Researchers employed a descriptive qualitative method in this study. The findings demonstrate the efforts made by the school to instill moral principles and prevent the three major sins in the educational system. These efforts include the school's daily morning recitations of the Pledge, the Dhuha Prayer, the Muroja'ah, and materials regarding adab. Aside from that, the school has a number of job programs and different approaches to issue resolution.The goal is to imbue pupils with moral principles, preventing the three major transgressions of education from progressing further.